Freeze-thaw durability of novel high early strength engineered cementitious composites - Schrag, Elliot D. (Kansas State University, 2020)
Concrete is susceptible to degradation due to freeze-thaw exposure, chemical attack, corrosion of embedded metals, thermal expansion, and drying and plastic shrinkage. By developing better high-performance concretes distresses from chemical, mechanical, and thermal loading can be further mitigated. High-performance concretes are characterized by their high strength and resistance to deterioration. This study investigates the durability of high-early-strength engineered cementitious composites (HES-ECC) which are known for their tensile ductility and high fracture toughness. The early strength gain was measured by conducting ASTM C39/C39M compressive strength tests and ASTM C496/C496M split tensile strength test at 4, 6, and 24 hrs. The testing showed promising results with compressive strengths above 3400 psi at six hours, and splitting tensile strengths of above 400 psi at six hours. Durability testing was also conducted by measuring the drying shrinkage according to ASTM C157/157M, freezing-and-thawing cycles according to ASTM C666/C666M, autogenous shrinkage, and adiabatic temperature rise. Measurements for the drying shrinkage test were taken at 3, 14, 28 days, 8, 10, 16, 32 weeks and resulted in high drying shrinkage due to the high cement content and absence of coarse aggregate in the mixtures. It is notable that for the mixture using Type III cement, specimens seem to expand between the 28 day test and eight and ten week tests. The mechanisms causing the expansion of the concrete are unclear but could be beneficial by reducing shrinkage cracking of concrete repairs. HES-ECC demonstrated little deterioration even after 300 freezing-and-thawing cycles. The autogenous shrinkage testing was conducted up to nine days, measuring the length change at various intervals throughout the duration of the test. Autogenous shrinkage up to approximately 0.14% length change was observed. HES-ECC reached temperatures above 176 °F for over ten hours which is concerning due to the potential of delayed ettringite formation. HES-ECC appear to be a promising repair material due to their resistance to freeze-thaw damage and high early strength development.
Keywords: Freeze-thaw durability; Composites; Cementitious; high-early-strength